Nitric oxide is not involved in Neisseria gonorrhoeae-induced cellular damage of human Fallopian tubes in vitro - KATHERINE P GARCÍA; PAULINA S RUBILAR; MACARENA F VARGAS; HUGO CÁRDENAS; MIGUEL A RIOS; PEDRO A ORIHUELA; RENATO H VARGAS; JUAN FUHRER; JOHN E HECKELS; MYRON CHRISTODOULIDES; LUIS A VELÁSQUEZ (Biological Research, 2010)
In the present study, we investigated whether cellular damage, as demonstrated by lactate dehydrogenase (LDH) release in the human fallopian tube (FT) infected by Neisseria gonorrhoeae (Ngo), correlated with high levels of nitric oxide synthase (NOS) mRNA and enzyme activity. Infection with Ngo induced a significant increase (~35-fold) in mRNA transcripts of the inducible isoform of NOS. Paradoxically, a reduction in NOS enzyme activity was observed in infected cultures, suggesting that gonococcal infection possibly influences translation of iNOS mRNA to the enzyme. In addition, treatment with the NOS inhibitor TRIM did not prevent gonococcal-induced cellular damage. In contrast, the addition of the inhibitor L-NAME induced a 40% reduction in LDH release, which correlated with a ~50% reduction in gonococcal numbers. Moreover, treatment of normal FT explants with an exogenous NO donor, SNAP, did not induce significant cellular damage. Taken together, our data suggest that NO does not contribute to cellular damage during infection of the human FT with Neisseria gonorrhoeae.